1996
DOI: 10.1136/bmj.312.7027.335
|View full text |Cite
|
Sign up to set email alerts
|

Disease in children infected with HIV in Abidjan, Cote d'Ivoire

Abstract: There is greater overlap between diseases associated with HIV infection and other common health problems in African children than there is in adults. Compared with adults, HIV positive children had a high prevalence of P carinii pneumonia and a low prevalence of tuberculosis. Measles, but not malaria, was associated with HIV infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
57
2
2

Year Published

1996
1996
2011
2011

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 153 publications
(64 citation statements)
references
References 18 publications
(21 reference statements)
3
57
2
2
Order By: Relevance
“…Several of the reported HIV-infected children with measles coinfections in the United States presented with either no rash or an uncharacteristic rash (18, 20, 61, 86, 97, 109), and 6 of the 19 reported cases resulted in death during the acute illness, usually caused by giant-cell pneumonia (32, 79). Several cases of MV encephalitis in HIV-infected individuals have also been reported (11,16,60,67,85,108,127). In fact, in an autopsy study of MV-infected patients in the Ivory Coast, MV was identified in the central nervous system in 3 of 13 HIV-infected patients and none of 5 non-HIV-infected patients (76).…”
Section: Infection In the Immunocompromised Hostmentioning
confidence: 99%
“…Several of the reported HIV-infected children with measles coinfections in the United States presented with either no rash or an uncharacteristic rash (18, 20, 61, 86, 97, 109), and 6 of the 19 reported cases resulted in death during the acute illness, usually caused by giant-cell pneumonia (32, 79). Several cases of MV encephalitis in HIV-infected individuals have also been reported (11,16,60,67,85,108,127). In fact, in an autopsy study of MV-infected patients in the Ivory Coast, MV was identified in the central nervous system in 3 of 13 HIV-infected patients and none of 5 non-HIV-infected patients (76).…”
Section: Infection In the Immunocompromised Hostmentioning
confidence: 99%
“…HIV-seropositivity rates among adults and children with tuberculosis range from 20-70%, and there are some countries such as Malawi and Zambia where HIV-seroprevalence rates are consistently above 50%. In Zambia and Cote d'Ivoire, HIV-seroprevalence rates in children aged 1 month to 14 years with tuberculosis are between 10-40%, with the highest overall age-specific HIVseroprevalence being found in children aged 1-4 years (Luo et al 1994;Lucas et al 1996a). In Zambia, one in four pregnant women are infected with HIV (Fylkesnes et al 1997).…”
Section: Tuberculosis and Hiv: Epidemiological Considerationsmentioning
confidence: 96%
“…An idea of the true risk of tuberculosis in these children may be obtained from autopsy studies. One such study in West Africa suggested a low risk (Lucas et al 1996a), but autopsies performed on HIV-positive children in Bulawayo, Zimbabwe (Ikeogu et al 1997), established a diagnosis of tuberculosis in 6 of 122 children (5%), and more recently a large autopsy study of children dying of respiratory illnesses in Zambia has shown that 20% of these children have tuberculosis across a wide range of age groups and HIV status.…”
Section: Tuberculosis In Hiv-infected Childrenmentioning
confidence: 97%
“…The appearance of chronic muco-cutaneous herpes simplex infection, oesophageal candidosis, chronic cryptosporidial diarrhoea, wasting syndrome and Kaposi's sarcoma were the commonest conditions de®ning entry of HIV-infected patients into WHO stage 4 (AIDS) in a Ugandan study of adults [3]. In contrast, in infants with AIDS, Pneumocystis carinii pneumonia is a common cause of morbidity and mortality [4], with up to 30% of children under 1 year having evidence of infection at post mortem [5].…”
Section: Introductionmentioning
confidence: 99%